Bilateral Renal Artery Thrombosis: A Rare Case of Severe Kidney Failure with Partial Recovery under Apixaban - Costa, Cláudia (2024)
Renal artery thrombosis is a rare and overlooked cause of kidney failure. Clinical presentation is unspecific, leading to delays in diagnosis and, therefore, preventing timely treatment. Herein, we present a case of bilateral renal artery thrombosis that led to severe acute kidney injury assumed to be irreversible. A 61‐year‐old Caucasian female presented to the emergency department with nausea, vomiting and reduction of urine output. Medical history was remarkable for an episode of acute right‐sided flank pain 3 months before, that resolved; long‐term exposure to corticosteroids; previous mild SARS‐CoV‐2 infection and history of smoking. Lab work showed se‐ rum creatinine (sCr) 7.5 mg/dL, (normal 3 months before). Renal ultrasound documented right kidney atrophy and small left kidney with reduction of parenchymal width. This led to an abdominal‐pelvic computed tomography that showed right renal artery occlusion with atrophic ipsilateral kidney and left renal artery occlusion with contrast enhancement maintained only on superior pole of the kidney. Renal damage was deemed irreversible by the Vascular Surgery team. Despite having initiated anticoagulation with enoxaparin, she evolved with need for dialysis. After 9 months under apixaban, she developed increasing diuresis and stable sCr 4.3 mg/dL, which allowed for hemodialysis (HD) suspension. We present a case of late diagnosed renal artery thrombosis that ended up with the need for renal replacement therapy. Clinical presentation with flank pain should raise suspicion for this usually overlooked condition, as prompt diagnosis and revascularization treatment are crucial to improve renal outcomes. Despite the delay in diagnosis and severity of the kidney injury, the patient presented a favorable outcome, with HD suspension, after 9 months of oral anticoagulation with apixaban. To our knowledge, this is the first case of bilateral renal artery thrombosis, treated with apixaban on monotherapy.